682 UNEXPECTED TRIGLYCERIDES-LOWERING EFFECT OF A NOVEL NUTRACEUTICAL COMPOUND FOR IBS. (15th December 2022) - Natale, Francesco; Loffredo, Francesco; Molinari, Riccardo; Covino, Simona; Alfieri, Roberta; Altobelli, Ippolita; Pezzullo, Enrica; Cimmino, Giovanni
Abstract: Background: In the last few years the role of gut microbiome in human health has been reported. Growing evidence indicate that it is linked to intestinatal diseases, such as the irritable bowel syndrome (IBS), and atherosclerotic disorders. The effect on lipid metabolism seems to be one of the potential mechanisms by which gut microbiome might favour the atherosclerotic process. IBS is a functional bowel disorder defined by the presence of recurrent episodes of abdominal pain associated with altered bowel habits. The severity of psychological and gastrointestinal symptoms in IBS has been linked with a distinct intestinal microbiota signature. In this retrospective study the effect of a novel nutraceutical compound, namely Triobiotix, on gastrointestinal symptoms in IBS patients has been evaluated. Effects on lipid profile have bee also recorded. Methods: Triobiotix is a nutraceutical consisting of: Maltodextrin; mineralized extract of Lithothamnion (Lithothamnion calcareum (Pallas) Areschoug, thallus dry extract); Bioecolians® gluco-oligosaccharides; Ferment mix (corn starch, Bifidobacterium animalis ssp. Lactis BLC1 (DSM 17741), Lactobacillus acidophilus LA3 (DSM 17742), Lactobacillus rhamnosus IMC 501 (DSM 16104), Lactobacillus paracasei Streptococc5 501 IMC102 SP4 (DSM 19385); short-chain fructo-oligosaccharides powder. The database of 40 Italian General Practitioners (GPs) were analyzed. At total of 587 patients with IBS and on Triobiotix were identified. Of these in only 535, a complete first and second control data was available. The primary endpoint of these analysis was to assess whether Triobiotix resulted in a reduction in pain and meteorism, thus resulting in a lesser intensity of the main gastrointestinal symptoms. Secondary endpoints were to look for significative changes in lab values of total cholesterol, triglycerides levels and glycaemia. Results: Treatment with Triobiotix for four weeks resulted in a reduction in the frequency and intensity of bloating, abdominal pain, and tenesmus. Unexpectedly, at the T1 control, mean cholesterol values were significatively reduced compared to the T0 evaluation. Triglycerides levels were also significantly decreased (186.37±66.4 vs. 176.13±67.9; p < 0.05). Conclusions: Our analysis showed an unexpected effect of this combination of micronutrients on lipid profile beyond IBS symptoms. However, further studies are needed to confirm this evidence and to evaluate the particular compound responsible of this effect. A goal of LDL-C less of 115mg/dL is desirable for patients at low to moderate CVR, a significative portion of population is far from this target. The discovery of novel micronutrients combinations with cholesterol lowering effects could be of great importance for the management of patients with low-moderate dyslipidaemia.